Linguistic continuity in software engineering. - Riehle, Richard (Software engineering notes.)
Many different concerns contribute to the complexity of software development. Some of these concerns are easy to spot. Others are right in front of us all along but not explicitly identified in a way that makes them intellectually accessible. We describe an idea that has always been in the background of awareness for programmers and software designers, but which seldom gets sufficient acknowledgement to be written about on its own. We call this linguistic [dis]continuity.